Nasya Karma and Nebulization: Bridging Ayurvedic Principles with Modern Drug Delivery. - Dikshit, Swarnkar; Lowkesh, Chandravanshi; Renuka, Nayak; singh, Jagat Vinit; Sanjay, Verma; Khuleshwar, Prasad (Journal of Neonatal Surgery, 2025)
Ashtang Ayurveda, the foundational framework of Ayurveda, comprises eight key elements. The Bal-Roga branch specifically addresses paediatric ailments. Despite the concurrent evolution of other medical disciplines, this approach was already in widespread use. Nebulization and Nasya represent two therapeutic modalities within this system. Both are used in medicine, although their administration and modes of action differ greatly. Medication can be administered via the nose via nasal insufflations, often known as Nasya. People typically use Nasya to eliminate doshas (disease-causing substances) that have accumulated or worsened in their heads and necks. Nebulization is a method of introducing aerosol—small, vaporized liquid droplets—into the lungs. This allows liquid medication, oxygen, and fluids to enter the lungs directly. The treatment of asthma has significantly changed thanks to inhalation therapy. (Aerosolized medication delivery or nebulization)..